UPAYA GERAKAN EXTINCTION REBELLION TERHADAP PERMASALAHAN PERUBAHAN IKLIM DI INGGRIS DAN INDONESIA - Pradwita, Intan Mulya; Retnaningsih, Umi Oktyari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Climate change has become a global issue, impacting countries around the world, such as the UK and Indonesia. Extinction Rebellion uses non-violent direct action as its strategy. Seeing the adverse effects that continue to occur due to climate change, a social movement called Extinction Rebellion emerged. This research discusses how the response and efforts made by the Extinction Rebellion activist movement in dealing with climate change that occurs in the UK and Indonesia. This research uses qualitative methods. Data was obtained from journals, official websites, books, and interviews with Extinction Rebellion activists. To analyze the data, the author uses the theory of new social movements. The research shows how Extinction Rebellion responds to climate change in the UK and Indonesia. Extinction Rebellion uses non-violent direct action (NVDA) as its main strategy. In the UK, XR has succeeded in realizing its first demand, which is to encourage the government to declare a climate emergency. Meanwhile, in Indonesia, XR is still continuing its efforts. Until 2023, XR in the UK and Indonesia will continue to make efforts and improve strategies until their goals are achieved. Keywords : Climate Change, Extinction Rebellion, New Social Movement